Collaborative networks strategies of transportation systems with RFID: a case study for a depot of empty containers - Pozo, Hamilton; Soares, Washington Luiz Pereira; Akabane, Getulo Kazue (Archives of Business Research, 2017)
This paper proposes ways to reduce operating costs for a Depot of empty containers, mainly to avoid wasting time with the separation of containers for cargo operations directed at offshore oil rigs. The methodology is exploratory and qualitative and looks at technological innovations such as Radio Frequency Identification (RFID). The technology is applicable in a depot of empty containers so that by using RFID solutions movements of containers on the backyard can better control the mobility and supply for critical situations such as offshore platforms that are located two hundred kilometers up the coastal port.